Study on The Structure of The Trees Population in The Maluka Riverside as A Subject Matter to Development of The Plants Ecological Handouts - Dharmono Putra; Mahrudin Mahrudin (Journal of Wetlands Environmental Management, 2020)
Understanding the population structure is one of the best ways to recognize the population in a plant as a whole. The riverside Maluka of Tanah Laut District is the swamps and river found herbs having an important role to play in maintaining the structure of the soil from the erosion of the river running on the area. Employing the descriptive method, this research attempts to describe population of structure plants of the riverside Maluka. The sample of structure plants are those on both edges of the riverside, namely: 1500 meters long and 2 meters wide. The data were collected by using the transect The results showed that there were 13 plants speciesÂ  trees with the different population structure. There are four plants with population structure of polygonnamely; Mangifera indica, Flacourtia rukam,Â  Antidesma Ghaesembilla, and Melaleuca cajuputi. There are six plants of width-based population structure of width, namely; Gluta renghas, Acacia auriculiformis, Syzygium sp., Syzygium guineense, Pisonia sp., Cassia alata. There are two plants in the forms of basin or pitcher, namely; Mangifera casturi and Fagraea crenulata. Plants that have population structure of reversed polygon is called Lagerstroemia speciosa.